Peningkatan Inovasi Pembelajaran dengan Penggunaan Media Berbasis Online Pada Guru Ekonomi SMA Kabupaten Kediri - Magistyo Purboyo Priambodo; Farida Rahmawati; Rizza Megasari; Nur Syahidah Binti Aulia; Santya Ulfah (Jurnal Pendidikan Ekonomi, 2022)
Facing the current digital era of information, learning activities tend to be done online, this causes changes in the education area that require educators to be able to provide learning through online media. Efforts to support these conditions require capacity building to improve the skills of teachers. The purpose of this study was to determine the teacher's needs for the ability of online learning media and what strategies can be done to improve the ability of teachers to use online learning media. The method used in this study is qualitative with a case study of high school economics teachers in Kediri Regency. The technique used is to provide training related to online learning media. This training is carried out through material presentation, as well as guidance and explanation or joint practice in making innovative learning media using Sparkol Videoscribe. This training activity aims to increase innovation by training teachers at SMA Kediri Regency using online-based media, namely Sparkol Videoscribe. The training participants amounted to 45 teachers who were members of the Economics Subject Teacher Community (MGMP) of Kediri Regency. As a result, the capacity building strategy with this training has been running optimally and has achieved its goals with indications that there has been an increase in the skills and understanding of teachers regarding online-based learning media. This is evidenced by the ability of participants to practice making media so that they can continue to be applied so that the learning developed can be more interesting and interactive.DOI: https://dx.doi.org/10.17977/UM014v15i22022p153